A+B+C=270 then sin2A-sin2B+sin2C
Answers
Answered by
12
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/dc6/887c527207f3a61439af385d6fad2908.jpg)
![](https://hi-static.z-dn.net/files/da5/534adb20881d95ad5de351da72f8677f.jpg)
Answered by
0
Answer:
sin2A-sin2B+sin2C = 2sin(A+C){cos(A-C) - cos(A+C)}
Step-by-step explanation:
A + B + C = 270° = 3π/2 = 2π - π/2 (GIVEN)
B+C = 2π - π/2 - A
sin(B+C) = sin(2π - π/2 - A ) = sin(- π/2 - A ) = - sin( π/2 + A ) = -cos(A)
sin(B+C) = - cos(A)
cos(B+C) = cos(2π - π/2 - A ) = cos(- π/2 - A) = cos(π/2 + A) = -sin(A)
cos(B+C) = -sin(A)
sin2A-sin2B+sin2C = sin2A + sin2C - sin2B
= 2sin(A+C)cos(A-C) - 2sinBcosB
= 2sin(A+C) cos(A-C) - 2sin(A+C) cos(A+C)
= 2sin(A+C){cos(A-C) - cos(A+C)}
sin2A-sin2B+sin2C = 2sin(A+C){cos(A-C) - cos(A+C)}
#SPJ3
Similar questions